The Correlation between Watching English Movies and Students’ Ability in Mastering Speaking Skill - Rahmatun Maulisa; Muchsin Muchsin; Faudi Faudi (English LAnguage Study and TEaching, 2023)
The purpose of this study was to find out whether there is a correlation between watching English movies and students’ ability in mastering speaking skill. This research was conducted with a quantitative correlational design. The participants of this study were 30 students from the English department at Universitas Serambi Mekkah, consisting of 11 students in semester 2, 9 students in semester 4, 2 students in semester 6, and 8 students in semester 8. In collecting the data, the researchers used questionnaires containing 40 items to measure the correlation between watching English movies and students’ ability in mastering speaking skill. The questionnaire of watching English movies consisted of 20 points with 3 items, while the questionnaire of students’ ability in mastering speaking skill consisted of 20 points with 4 items. The results showed that the r-count is higher than the r-table value (0.971 0.361). Thus, H0 is rejected, and Ha is accepted. This means that there is a correlation between watching English movies and students' ability in mastering speaking skill.